Invisible Disabilities: Unique Challenges for Employees and Organizations. Issue 2 (June 2014) - Santuzzi, Alecia M.; Waltz, Pamela R.; Finkelstein, Lisa M.; Rupp, Deborah E.
Abstract Workers with invisible disabilities encounter unique challenges compared to workers with other concealable identities and even workers with visible disabilities. These challenges occur not only in the decisions of whether to disclose the invisible disability in the workplace but also in the detection and acceptance of having a disability to disclose. Disclosure of disabilities in the workplace likely has implications for the individual worker's health, social relationships, and work performance as well as for an employing organization's outcomes. We argue that current legislation and policies might not be sensitive to the unique experiences and disclosure decisions faced by workers with invisible disabilities. We invite researchers and practitioners to consider adjustments to current legislation and workplace practices in order for employing organizations to account for the unique challenges facing workers with invisible disabilities and fully accommodate those workers.